PENDAMPINGAN PEMBUATAN BONEKA JARI BERBAHAN DASAR LIMBAH PUNTUNG ROKOK SEBAGAI MEDIA PEMBELAJARAN BAGI SMB MULYA DHARMA - Sukanto Sukanto; Rini Setiani; Ariek Devin Samanta; Rakay Indramayapanna (Yayasan Education and Social Center, 2023)
Finger puppet learning media made from cigarette butt waste is a 3D learning media that can be a concrete teaching tool and can facilitate student understanding. This program aims to assist in making finger puppets made from cigarette butt waste for SMB Mulya Dharmma educators as a learning medium. The method used in the implementation of this program is carried out through three stages, namely the preparation stage, the implementation stage, and the evaluation stage. In the preparation stage, proposals, field observations, interviews, documentation, and socialization are carried out. At the implementation stage, sterilization of cigarette butt waste and finger puppetry made from cigarette butt waste were carried out. And at the evaluation stage, filling out a questionnaire was carried out, where the results were 85.44. From this value, it is known that the level of participant satisfaction with the implementation of this program is quite high. From the results of the evaluation, it is known that this program has been quite successful. The result of this program is a learning media in the form of finger puppets made from cigarette butt waste